Free Chinese immigration to South Africa in the twentieth century: survival and opportunity - Xiao, Xin (Department of Historical Studies, 2017)
This thesis focuses on the Chinese free immigrants to South Africa from 1904 to the present. It charts the volume and flow of Chinese immigrants, as well as the relationship between different groups of Chinese immigrants and the relationship between Chinese immigrants and local communities where they settled. It demonstrates that Taiwanese immigrants had stronger capability sets than earlier mainland Chinese immigrants. It shows that due to their relatively strong economic background, Taiwanese immigrants' livelihoods were more rewarding than those of mainland Chinese immigrants. Taiwanese immigrants were also more adept at dealing with the South African government and at running their own businesses, particularly during the apartheid era.